Urban pseudonym changing strategy for location privacy in VANETs. (2017) - Boualouache, Abdelwahab; Moussaoui, Samira
The development of an effective pseudonym changing strategy to protect the location privacy of the vehicular adhoc network's (VANET's) users is still an open problem in the literature. In this paper, we first propose a comparison between the existing pseudonym changing strategies. This comparison is based on their effectiveness to prevent the pseudonyms linking attacks and based on the costs involved in changing a pseudonym. We also propose a new pseudonym changing strategy adapted for the urban environment, called urban pseudonym changing strategy (UPCS). UPCS is based on the construction of silent mix zones (SMs) at signalised intersections. UPCS can be configured to use either pseudonyms changing technique or pseudonyms exchanging technique inside these SMs. The analyses show a good level of prevention against the pseudonyms linking attacks. The performances are evaluated in various vehicular scenarios. The obtained results show high levels of location privacy protection can be achieved using UPCS with pseudonyms changing configuration.